STUDY OF LANGUAGE VARIATION ON PRODUCT PROMOTION ADVERTISING ON INSTAGRAM - Afi Fadillah; Windy Fitra Fitra Hardianti (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Language is very common in various media, one of which is in advertising. The use of attractive language can attract attention for those who see it. This is also done by the company Kirihuci Indonesia in marketing Cilembu sweet potato processed products on the Instagram social network. To find out what language variations are used in the advertisement for Kirihuci's sweet potato products on Instagram, this research was conducted. This study uses a qualitative descriptive method with interviews and internet searching as data collection techniques. After the linguistic data was collected, a content analysis was carried out to describe the results of the linguistic data collection. From this study, it was found that Kirihuci used sociolect variations as a variation of advertising language, because it relates to the status, class, and social class of the speakers. As a seller who wants to get closer to potential consumers, the Kirihuci Instagram manager uses colloquial variations or variations of casual language that are commonly used in everyday life. The use of Sundanese is also used as a form of Kirihuci's identity as a typical ethnic product of Bandung.